2013
DOI: 10.1371/journal.pbio.1001583
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Remodeling of Tip Links Underlies Mechanosensory Regeneration in Auditory Hair Cells

Abstract: Backscatter scanning electron microscopy and conventional whole cell patch-clamp experiments reveal a two-step mechanism for the regeneration of tip links, the crucial element of mechanotransduction machinery in the hair cells of the inner ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(172 citation statements)
references
References 53 publications
11
155
2
Order By: Relevance
“…The fluid jet was preferred to a rigid probe (17,19) because it does not require any direct contact with the stereocilia, which could affect their resting position and also damage some of the interciliary links (16). Unless the shape of the probe is perfectly matched to that of the V-or U-shaped bundle of the OHCs or IHCs, respectively, this method would also lead to nonuniform displacement of individual stereocilia (16,25,26). Such uniformity is achieved with fluid jet stimulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid jet was preferred to a rigid probe (17,19) because it does not require any direct contact with the stereocilia, which could affect their resting position and also damage some of the interciliary links (16). Unless the shape of the probe is perfectly matched to that of the V-or U-shaped bundle of the OHCs or IHCs, respectively, this method would also lead to nonuniform displacement of individual stereocilia (16,25,26). Such uniformity is achieved with fluid jet stimulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantage of the rigid probe, compared with the fluid jet, is that it requires optimal vertical and angular positioning to produce a homogeneous displacement of the V-or Ushaped hair bundle of OHCs and IHCs, respectively. Because the glass probe may not contact some stereocilia, when the probe is displaced (16,25), all stereociliary rows are initially deflected by viscous coupling, but then those not in direct contact with the probe relax, producing an artifactual adaptation (see also Materials and Methods). Indeed, it has been demonstrated that when the vertical positioning of the rigid probe was not optimal in respect to the bundle of cochlear OHCs, it produced an artifactually large and Ca 2+ -independent MET current decay (25), similar to that observed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic structural evaluation revealed that the first and second ectodomains of cadherin 23 and protocadherin 15 interact with each other in a "handshake" mode to form the tip-link filaments (31). The current hypothesis is that the mature tip links are formed by protocadherin 15 and cadherin 23 (21), although during regeneration the transient but functional tip links are made of two protocadherin 15 isoforms (18). USH proteins myosin VIIa, harmonin, and sans are also found at the upper attachment of the tip link (9,12,15).…”
mentioning
confidence: 97%
“…Two closely related pcdh15 genes have been identified in zebrafish (Seiler et al, 2005), with Pcdh15a involved in hearing and vestibular functions presumably through the formation of the tip links that gate the mechanotransduction channels, as is the case in mammalian hair cells (Kazmierczak et al, 2007;Indzhykulian et al, 2013). We generated Pcdh15a MOs and tested them for dye uptake impairment.…”
Section: Characterization Of Clarin-1 Mosmentioning
confidence: 99%